2018
DOI: 10.1002/jcp.26614
|View full text |Cite
|
Sign up to set email alerts
|

Testin was regulated by circRNA3175‐miR182 and inhibited endometrial epithelial cell apoptosis in pre‐receptive endometrium of dairy goats

Abstract: Circular RNAs (circRNAs) in various tissues and cell types from mammalian sources have been studied. However, present knowledge on circRNAs in the development of pre-receptive endometrium (PE) in dairy goats is limited. In the pre-receptive endometrium of dairy goats, higher circRNA3175 (ciR3175) levels, lower miR-182 levels and higher Testin (TES) levels were detected. And ciR3175 could decreased the miR-182 levels by acting as a miRNA sponge, and miR-182 could down-regulated the expression level of TES via t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 50 publications
(63 reference statements)
0
17
0
Order By: Relevance
“…Circular RNAs (circRNAs) can act as posttranscriptional regulators by sponging miRNAs (Memczak et al, 2013), and some circRNAs may have important roles in CEEC and RE establishment (L. L. Zhang, Liu, Ma, et al, 2018).…”
mentioning
confidence: 99%
“…Circular RNAs (circRNAs) can act as posttranscriptional regulators by sponging miRNAs (Memczak et al, 2013), and some circRNAs may have important roles in CEEC and RE establishment (L. L. Zhang, Liu, Ma, et al, 2018).…”
mentioning
confidence: 99%
“…Recently, circRNAs have also been suggested to constitute a subpopulation of ceRNAs that can act similar to a sponge and absorb miRNAs by base complementary pairing, thereby regulating the expression of miRNA target genes. For example, Zhang et al (2018) found in the prereceptive endometrium of dairy goats that ciR3175 can reduce the level of miR-182 by acting as a sponge of miRNA, and miR-182 can downregulate TES in endometrial epithelial cells (EECs) through the target site, as predicted, in vitro . In this way, ciR3175 acts as a ceRNA that isolates miR-182, thereby protecting TES transcripts from miR-182-mediated EEC inhibition in vitro .…”
Section: Competitive Endogenous Rna Mechanisms Of Actionmentioning
confidence: 77%
“…Primary dairy goat endometrial epithelial cells (gEECs) were isolated and purified by digestion of trypsin, centrifugation, and difference in tempo adherence (L. Zhang et al, , ) and observed by a light microscope (X. Qi et al, ; X.F. Qi et al, ).…”
Section: Methodsmentioning
confidence: 99%